A single-step fabrication of CoTe2 nanofilm electrode toward efficient overall water splitting. (1st June 2019) - Yin, Yaqing; Xu, Jun; Guo, Wei; Wang, Zhao; Du, Xiaodi; Chen, Chan; Zheng, Zijian; Liu, Dan; Qu, Deyu; Xie, Zhizhong; Tang, Haolin; Li, Junsheng
Abstract: Development of efficient and inexpensive full water splitting electrocatalyst through a facile procedure is required for many renewable energy conversion devices. Herein, a nickel foam supported CoTe2 nanofilm electrode is successfully introduced via a single-step hydrothermal process. As revealed by density function theory studies, the unique electronic configuration of CoTe2 endows the material with a high density of state near Fermi level favorable for charge transfer in catalytic reactions. This structural merit along with the high electrochemical active surface area of the novel CoTe2 nanofilm electrode enable a high activity of the electrode for both hydrogen evolution and oxygen evolution reactions. A full water splitting device with the CoTe2 nanofilm electrode as both anode and cathode could reach a current density of 10 mA cm −2 at a low potential of 1.605 V. Furthermore, a good stability of the bifunctional catalyst is also demonstrated.